A phylogenetic analysis of Brycon and Henochilus (Characiformes, Characidae, Bryconinae) based on the mitochondrial gene 16S rRNA - Hilsdorf, Alexandre Wagner Silva; Oliveira, Claudio [UNESP]; de Lima, Flávio César Thadeo; Matsumoto, Cristianne Kayoko (FapUNIFESP (SciELO), 2008)
The genus Brycon, the largest subunit of the Bryconinae, has 42 valid species distributed from southern Mexico to the La Plata River in Argentina. Henochilus is a monotypic genus, comprising a single species (H. wheatlandii) found in the upper Rio Doce basin. In the present study, partial sequences of the mitochondrial gene 16S were obtained for fifteen species of Brycon and for Henochilus wheatlandii. The results showed that the genus Brycon is paraphyletic, since Henochilus is the sister-group of B. ferox and B. insignis. The most basal species analyzed were the trans-Andean species B. henni, B. petrosus, and B. chagrensis. Copyright © 2008, Sociedade Brasileira de Genética.
Keywords: Fish evolution; Mitochondrial DNA; Molecular systematics; Phylogeny; Systematic